Putin and the Nuclear Dimension to Russian Strategy. Issue 4 (1st October 2016) - Cimbala, Stephen J.; McDermott, Roger N.
ABSTRACT: Nuclear weapons and nuclear strategy have found themselves as parts of the discussions among expert and other commentators about the future of Russian President Vladimir Putin and about Russia's military-strategic options in Europe following its annexation of Crimea and destabilization of Eastern Ukraine. This study considers some of the nuclear-related aspects of Putin's and Russia's survivability with respect to: (1) principal challenges for NATO in the face of improving Russian military capabilities and plausible strategies, (2) the future relationship between Russia's conventional military and nuclear capabilities and military-strategic priorities, and (3) assessment of Russia's threat perceptions in the context of its 'strategic history'.